2020
DOI: 10.3390/microorganisms8111747
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Species–Area Relationships in Antarctic Cryoconite Holes Depend on Productivity

Abstract: The island species–area relationship (ISAR) is a positive association between the number of species and the area of an isolated, island-like habitat. ISARs are ubiquitous across domains of life, yet the processes generating ISARs remain poorly understood, particularly for microbes. Larger and more productive islands are hypothesized to have more species because they support larger populations of each species and thus reduce the probability of stochastic extinctions in small population sizes. Here, we disentang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…Likewise, Chlorococcum sp., the most abundant algal phylotype in crusts was also the most common alga in cryoconite holes of the valley (Sommers et al, 2019a). This link is also seen with heterotrophic bacterial genera common in our soils (e.g., Sphingomonas, Blastocatella) that were also found in high relative abundance in cryoconite holes across Taylor Valley (Sommers et al, 2020). Although an in-depth analysis of the comparisons between terrestrial mountain habitats and cryoconite hole sediments is beyond the scope of this paper, more investigation into whether high-elevation soils are the main source of inoculum for cryoconite holes is warranted.…”
Section: Broader Relevance Of This Studysupporting
confidence: 72%
“…Likewise, Chlorococcum sp., the most abundant algal phylotype in crusts was also the most common alga in cryoconite holes of the valley (Sommers et al, 2019a). This link is also seen with heterotrophic bacterial genera common in our soils (e.g., Sphingomonas, Blastocatella) that were also found in high relative abundance in cryoconite holes across Taylor Valley (Sommers et al, 2020). Although an in-depth analysis of the comparisons between terrestrial mountain habitats and cryoconite hole sediments is beyond the scope of this paper, more investigation into whether high-elevation soils are the main source of inoculum for cryoconite holes is warranted.…”
Section: Broader Relevance Of This Studysupporting
confidence: 72%
“…A Qubit assay was used to quantify all DNA concentrations prior to DNA amplification. Extracted DNA concentrations were standardized to 1 g of dry soil to serve as a proxy for microbial biomass (Sommers et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…There are additional community assembly theories such as the island species-area relationships (MacArthur and Wilson 1967) which describes the macroecological pattern of an increase in number of species with an increase in area of an island. Sommers et al 2020 showed that relationship Fig. 7 CCA of eukaryote community composition for absolute counts of OTUs.…”
Section: Of Terrestrial Ponds On Ross Island and Mcmurdo Drymentioning
confidence: 99%
“…The highest richness was found in Conophyton Pond, which was one of the smaller ponds, and Duet Pond with the largest area had the median richness, with Salt Pond being of medium size having the lowest richness. However, a larger number of samples and bigger range of habitat areas would be needed to be able to apply the mathematical model as done in the study by Sommers et al (2020).…”
Section: Of Terrestrial Ponds On Ross Island and Mcmurdo Drymentioning
confidence: 99%